Flight evaluation of a sliding mode online control allocation scheme for fault tolerant control. (April 2020) - Chen, Lejun; Edwards, Christopher; Alwi, Halim; Sato, Masayuki
Abstract: This paper develops a sliding mode fault tolerant control scheme based on a Linear Parameter Varying (LPV) system representation of the plant. The scheme includes a control allocation component, which is capable of utilizing the available healthy actuators in the face of actuator faults/failures, in an effort to retain close to nominal fault free performance. The proposed scheme is validated using the Japan Aerospace Exploration Agency's Multi-Purpose Aviation Laboratory (MuPAL- α ) research aircraft. The flight test results demonstrate good lateral-directional state tracking performance with no visible performance degradation in the presence of rudder and aileron faults.